2014
DOI: 10.1093/jxb/eru297
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a novel Arabidopsis PP2C isoform, AtPP2CF1, enhances plant biomass production by increasing inflorescence stem growth

Abstract: In contrast to mammals, higher plants have evolved to express diverse protein phosphatase 2Cs (PP2Cs). Of all Arabidopsis thaliana PP2Cs, members of PP2C subfamily A, including ABI1, have been shown to be key negative regulators of abscisic acid (ABA) signalling pathways, which regulate plant growth and development as well as tolerance to adverse environmental conditions. However, little is known about the enzymatic and signalling roles of other PP2C subfamilies. Here, we report a novel Arabidopsis subfamily E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…Additionally, compared to wild-type plants, the TAQed mutants showed a 40% increase in biomass (dry weight of aerial parts) (Fig. 4e ) 26 . Importantly, the relative distribution of stem lengths in the 81 TAQed tetraploid (TQ4) plants was significantly broader ( P < 0.01, F -test) than that in the 40 TAQed diploid (TQ2) plants (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, compared to wild-type plants, the TAQed mutants showed a 40% increase in biomass (dry weight of aerial parts) (Fig. 4e ) 26 . Importantly, the relative distribution of stem lengths in the 81 TAQed tetraploid (TQ4) plants was significantly broader ( P < 0.01, F -test) than that in the 40 TAQed diploid (TQ2) plants (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Protein phosphatase 2C (PP2C) is a key player in the ABA signalling. Studies showed that PP2C was inhibited by ABA (Park et al, ) and an overexpression of a PP2C isoform was able to activate cell proliferation and expansion (Sugimoto et al, ). Our transcriptome data revealed that a gene encoding PP2C was up‐regulated in phytoplasma‐infected leaves of sweet cherry.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, EGR-mediated regulation of proline accumulation was MASP1 independent and EGR2 also had some effect to enhance MT stability and alleviate root swelling independently of MASP1. An effect of EGR1 on inflorescence growth, as well as characterization of EGR1 phosphatase activity, has been reported (Sugimoto et al, 2014); however, there has been no reported mechanism of EGR action or analysis of EGR stress function. Likewise, our data show that MASP1 is a MT binding protein.…”
Section: Egr-masp1 Function In Mt Regulation Growth Regulation and mentioning
confidence: 99%
“…An important aspect of drought-related signaling is the activity of Type 2C protein phosphatases (PP2Cs), especially the Clade A PP2Cs whose activity is regulated by interaction with Pyrabactin Resistant-Like/Regulatory Component of Abscisic Acid Receptor (PYL/ RCAR) ABA receptors (Cutler et al, 2010;Fuchs et al, 2013). Interaction with PYLs is specific to Clade A PP2Cs, which account for only nine of the 80 PP2Cs present in Arabidopsis (Arabidopsis thaliana; Fuchs et al, 2013;Sugimoto et al, 2014). For most of the other PP2Cs in Clades B to F, there is little information on their physiological function or on the phosphorylation sites they regulate.…”
Section: Introductionmentioning
confidence: 99%